Erozja zwałowisk pokopalnianych w rejonie Łęknicy = Erosion of post-mining heaps in Łęknica region - Greinert, Henryk; Greinert, Andrzej; Drab, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Paper presents the physical and chemical proprieties of soil on the heaps of former lignite mine "The friendship of Nations", in Łęknica region. Unfavourable for plants proprieties of grounds as the consequence of wrong executed reclamation works on described terrain were the cause of strong superficial water erosion as well as ravine erosion.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); zwałowiska pokopalniane; erozja wodna; post-mining heaps; water erosion